Experimental study on the impact of double tilted Venetian blinds on indoor daylight conditions. (November 2022) - Gomes, M. Glória; Santos, A.J.; Calhau, M.
Abstract: One of the most important concerns when designing buildings as liveable spaces is the indoor comfort. This depends on different factors, including daylight availability and discomfort glare conditions. The increasing use of glazing areas in the building's envelopes can lead to high energy consumption and problems such as visual discomfort. The use of shading devices stands out as a sustainable design strategy to reduce energy consumption in the buildings. This work presents an experimental analysis of the impact of an innovative shading device, a double-tilted venetian blind (DTVB) with different positions of upper and lower slats, on the indoor daylight conditions. Moreover, discomfort glare evaluation, through DGPs metric, is performed. The experimental campaign was conducted in an outdoor test cell during three periods of the year: summer solstice, winter solstice and autumn equinox. Experiments were carried out with both white and grey DTVBs, for several positions of upper and lower slats, under clear and overcast sky conditions. This comprises the measurement of indoor and outdoor horizontal and vertical illuminances and irradiances and solar and visible transmittance of the fenestration. It was concluded that DTVBs can achieve a higher performance, regarding solar protection, daylighting and glare control, when compared with more traditional venetian blinds systems. Highlights: Experimental daylight performance study of an innovative shading device. A double tilted venetian blind (DTVB) with different slats angles was studied. Daylighting parameters were measured in a test cell. White and grey DTVB slats were evaluated under clear and overcast sky conditions. DTVB have higher daylight efficiency than traditional Venetian blinds.